The Kingfisher soccer encyclopedia - Gifford, Clive (Kingfisher : Distributed in the U.S. by Macmillan, 2010)
Covers the sport's rules, skills, fans and the media, coaches, and tactics, and offers profiles of the top players and teams. From the first soccer games to today's money-spinning global industry, the book takes readers to the heart of a sport that is played and watched by millions of people around the world. It explains the key rules, skills, and tactics and examines issues in and around the game--supporters, the media, and the demands of being a professional player. Stunning digital artwork recreates some of the most famous moves and greatest goals in soccer history, and the latest statistics are provided for soccer enthusiasts.